2006
DOI: 10.1227/01.neu.0000209638.62401.7e
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Neurocognitive Decline after Carotid Endarterectomy

Abstract: OBJECTIVE-Although the incidence of stroke after carotid endarterectomy (CEA) is low (1-3%), approximately 25% of patients experience subtle declines in postoperative neuropsychometric function. No studies have investigated the risk factors for this neurocognitive change. We sought to identify predictors of postoperative neurocognitive dysfunction.METHODS-We enrolled 186 CEA patients, with both symptomatic and asymptomatic stenosis, to undergo a battery of neuropsychometric tests preoperatively and on postoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
2
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 36 publications
4
68
2
1
Order By: Relevance
“…The association between diabetes mellitus and post-operative injury was rein-forced by our data. Additionally, we found smoking history to be linked with favorable outcome, although this relationship was not observed in prior, larger studies [17]. Percent change in peri-operative MCP-1 levels, however, demonstrated the strongest correlation with outcome in our multivariate analysis.…”
Section: Discussioncontrasting
confidence: 85%
See 4 more Smart Citations
“…The association between diabetes mellitus and post-operative injury was rein-forced by our data. Additionally, we found smoking history to be linked with favorable outcome, although this relationship was not observed in prior, larger studies [17]. Percent change in peri-operative MCP-1 levels, however, demonstrated the strongest correlation with outcome in our multivariate analysis.…”
Section: Discussioncontrasting
confidence: 85%
“…Chronic inflammation and small vessel disease likely render patients susceptible to neuronal injury following global cerebral hypoperfusion. Our group has demonstrated that advanced age and history of diabetes mellitus are independent predictors of neurocognitive outcome following CEA [17]. We have also shown that elevated preoperative monocyte count independently predicts neuropsychological decline [16].…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations